Enantiospecific effects of ketoconazole on aryl hydrocarbon receptor - Novotna, Aneta; Korhonova, Martina; Bartonkova, Iveta; Soshilov, Anatoly A; Denison, Michael S; Bogdanova, Katerina; Kolar, Milan; Bednar, Petr; Dvorak, Zdenek (PloS one, 2014)
Azole antifungal ketoconazole (KET) was demonstrated to activate aryl hydrocarbon receptor (AhR). Since clinically used KET is a racemic mixture of two cis-enantiomers (2R,4S)-(+)-KET and (2S,4R)-(-)-KET, we examined the effects of KET enantiomers on AhR signaling pathway. (+)-KET dose-dependently activated AhR in human gene reporter cell line AZ-AHR, and displayed 5-20× higher agonist activity (efficacy), as compared to (-)-KET; both enantiomers were AhR antagonists with equal potency (IC50). Consistently, (+)-KET strongly induced CYP1A1 mRNA and protein in human HepG2 cells, while (-)-KET exerted less than 10% of (+)-KET activity. In primary human hepatocytes, both enantiomers preferentially induced CYP1A2 over CYP1A1 mRNA and protein, and the potency of (+)-KET was slightly higher as compared to (-)-KET. Ligand binding assay with guinea pig liver cytosols revealed that both (+)-KET and (-)-KET are weak ligands of AhR that displaced [3H]-TCDD with comparable potency. Similarly, both enantiomers weakly transformed AhR to DNA-binding form with similar potency, as showed by EMSA, in guinea pig liver cytosolic extracts and nuclear extracts from mouse Hepa-1 cells. We also examined effects of KET on glucocorticoid receptor (GR), a regulator of AhR activity. Both KET enantiomers antagonized GR with similar potency, as revealed by gene reporter assay in AZ-GR cell line and down-regulation of tyrosine aminotransferase mRNA in human hepatocytes. Finally, we demonstrate enantiospecific antifungal activities of KET enantiomers in six Candida spp. strains. In conclusion, the significance of current study is providing the first evidence of enatiospecific effects of cis-enantiomers of ketoconazole on AhR-CYP1A pathway.
Keywords: hepatocyty; Animals; Hep G2 Cells; Antifungal Agents; Female; buňky Hep G2; ženské pohlaví; Transcription, Genetic; Structure-Activity Relationship; lidé; receptory aromatických uhlovodíků; Mice; signální transdukce; messenger RNA; stereoizomerie; Stereoisomerism; Cytochrome P-450 CYP1A1; myši; Signal Transduction; morčata; Hepatocytes; RNA, Messenger; genetická transkripce; ketokonazol; Receptors, Aryl Hydrocarbon; Ketoconazole; Cytochrome P-450 CYP1A2; Male; Aged; cytochrom P-450 CYP1A1; vztahy mezi strukturou a aktivitou; Guinea Pigs; Candida; lidé středního věku; senioři; zvířata; cytochrom P-450 CYP1A2; mužské pohlaví; antifungální látky; Middle Aged; Humans